Bond behavior between basalt fiber‐reinforced polymer rebars and coral‐reef‐sand concrete conditioned in saline solution. (24th October 2019) - Ding, Lining; Shi, Jianzhe; Wang, Xin; Liu, Ying; Jin, Yundong; Wu, Zhishen
Abstract: This paper studies the bond behavior between basalt fiber‐reinforced polymer (BFRP) rebars and coral‐reef‐sand (CRS) concrete exposed to a saline environment. The gradation and mix proportion of CRS concrete was firstly selected, through compressive tests on CRS concrete cubes. A series of pullout tests were conducted on a total of 84 pullout specimens after conditioning in a saline solution. The experimental variables included type of rebar (steel and BFRP), diameter of BFRP rebar, conditioning duration and temperature, and type of conditioning (continuous immersion and wet–dry cycle). The stress–slip curves and bond strength of the pullout specimens were analyzed and discussed. The results show that 0.54 is selected as the water/cement ratio for CRS concrete, among the range of analyzed concrete mixes. The bond behaviors of BFRP rebars depend on their diameter. BFRP rebars with 12‐mm‐diameter have the best bond durability after conditioning in a saline solution, when compared with their counterparts with 8‐ and 16‐mm‐diameters. The effects of conditioning temperature and type of conditioning on the bond behavior of 12‐mm‐diameter BFRP rebar are negligible. A design‐oriented formula was proposed for the prediction of the development length of a BFRP rebar in CRS concrete based on the experimental data. Furthermore, modified BPE models were calibrated to describe the bond–slip relationship of BFRP rebars in CRS concrete in a saline environment.